Challenges for environmental governance: policy issue interdependencies might not lead to collaboration - Hedlund, Johanna (Stockholm University, 2022)
Policy actors address complex environmental problems by engaging in multiple and often interdependent policy issues. Policy issue interdependencies imply that efforts by actors to address separate policy issues can either reinforce (‘win-win’) or counteract (‘trade-off’) each other. Thus, if interdependent issues are managed in isolation instead of being coordinated, the most effective and well-balanced solution to the underlying problem might never be realised. This study asks if reinforcing and counteracting interdependencies have different impacts on perception and collaboration. Our empirical study of collaborative water governance in the Norrström basin, Sweden, shows that policy actors often avoid collaborating when the policy issues exhibit reinforcing interdependencies. Our evidence indicates a perceived infeasibility of acting on reinforcing interdependencies. We also find that actors do not consider counteracting interdependencies (‘trade-offs’) at all when they engage in collaboration. Further, even though actors were aware of counteracting and reinforcing interdependencies, our analyses suggest they might be less aware of the former. These findings illustrate that actors either avoid each other due to policy issue interdependencies or, at best, ignore existing interdependencies when engaging in collaboration. Our study highlights the importance of problem perception in accomplishing integrated solutions to complex environmental problems, and of how understandings of different types of interdependencies shape collaboration in environmental governance.

This dataset consists of social network analysis data and policy issue network data. Network data consists of nodes (rows and columns) and links (matrix cells). In the social network data, rows and columns represent actors and matrix cells their collaboration. 1 indicates collaboration, 0 indicates no collaboration. In the policy issue network data, rows and columns represent policy issues, and matrix cells their reinforcing or counteracting interdependencies. Two different policy issue networks (one reinforcing and one counteracting) are represented. The actor-issue file reports the engagement of an actor in a given issue, i.e. that the actor works with that specific issue. The data also includes an actor attribute file, where each row represents the same actor as in the social network data and each column a specific attribute that might characterise the actor (1-yes,0-no). The data files are compatible with the free software MpNet (http://www.melnet.org.au/pnet), and for running Exponential Random Graph Models.

For more information see: Hedlund, J., Nohrstedt, D., Morrison, T. et al. Challenges for environmental governance: policy issue interdependencies might not lead to collaboration. Sustain Sci (2022). DOI: https://doi.org/10.1007/s11625-022-01145-8

Policyaktörer bemöter komplex miljöproblem genom att engagera sig i flera, ofta sammankopplade ("interdependenta"), policyfrågor. Interdependens mellan policyfrågor kan innebära att arbete att hantera skilda policyfrågor antingen stärker (synergi) eller motverkar (målkonflikt) varandra. Om interdependenta frågor hanteras isolerat istället för att koordineras kan det dock hindra att de mest effektiva och välbalanserade lösningarna till grundläggande problem genomförs. Den här studien undersöker om stärkande och motverkande interdependenser har olika påverkan på aktörers perception och samverkan. Vår empiriska studie av samverkan inom vattenförvaltningen av Norrströms avrinningsområde, Sverige, visar att policyaktörer ofta undviker att samarbeta om synergier. Vårt material indikerar att aktörer ofta upplever att det inte är möjligt att agera på synergier. Vi finner också att aktörer ofta inte tar hänsyn till målkonflikter alls när de samverkar. Trots att aktörer var medvetna om målkonflikter och synergier antyder vår analys att de är mindre medvetna om den förra. Dessa resultat indikerar att aktörer antingen undviker varandra på grund av interdependens mellan policyfrågor eller, i bästa fall, ignorerar existerande interdependenser i samverkan. Vår studie belyser vikten av problemperception för att åstadkomma integrerade lösningar på komplexa miljöproblem, och av hur förståelser för olika typer av interdependens påverkan samverkan i miljöförvaltning.

Se engelska katalogsidan för beskrivning av datasetet.
Utmaningar för miljöförvaltning: interdependens mellan policyfrågor leder inte alltid till samverkan
Keywords: Administrative units; Administrativa enheter; environmental governance; miljöförvaltning; collaborative governance; samverkan; network analysis; nätverksanalys; water governance; vattenförvaltning; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Natural landscapes; Naturlandskap; Government, political systems and organisations; Regering, politiska system och organisationer; Environmental Sciences; Miljövetenskap; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; Public Administration Studies; Studier av offentlig förvaltning